Isolation of Isoaurone from the Tobacco Stem and its Anti-tobacco Mosaic Virus Activity - Liu, Zhihua; Hang, Jingmei; Zhao, Wei; Duan, Yuanxing; Wan, Yaming; Miao, Mingming (Asian Journal of Chemistry, 2013)
A new isoaurone, 4,4'-dimethoxy-6-O-b-D-glucopyranosyl-isoaurone (1), were isolated from the tobacco stem. The structure of 1 was elucidated by spectroscopic methods including 1D- and 2D-NMR techniques. Compound 1 was also evaluated for its anti-tobacco mosaic virus (anti-TMV) activity and it showed high anti-tobacco mosaic virus activity with inhibition rate of 31.5 %. This valve is higher than that of positive control, ningnanmycin (28.4 %).